2019
DOI: 10.1152/ajpgi.00284.2018
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-33a prevents epithelial-mesenchymal transition, invasion, and metastasis of gastric cancer cells through the Snail/Slug pathway

Abstract: Invasion and metastasis are responsible for the majority of deaths in gastric cancer (GC). microRNA-33a (miR-33a) might function as a tumor suppressor in multiple cancers. Here, we describe the regulation and function of miR-33a in GC and mechanisms involved in epithelial-mesenchymal transition (EMT) and metastasis. First, GC tissues and adjacent normal tissues were collected. miR-33a upregulation or SNAI2 depletion on GC cells were introduced to assess the detailed regulatory mechanism of them. We assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…We also provided evidence that SNAI2 could stimulate the expression of intestinal markers in gastric cells and primary cultured cells. These results are partly consistent with some studies showing that SNAI2 promotes the malignant transformation of gastric cells through an EMT dependent manner [36][37][38][39]. Nevertheless, in this study, we rst identi ed that SNAI2 was augmented in IM tissues and could promote the expression of intestinal markers in gastric cells.…”
Section: Discussionsupporting
confidence: 92%
“…We also provided evidence that SNAI2 could stimulate the expression of intestinal markers in gastric cells and primary cultured cells. These results are partly consistent with some studies showing that SNAI2 promotes the malignant transformation of gastric cells through an EMT dependent manner [36][37][38][39]. Nevertheless, in this study, we rst identi ed that SNAI2 was augmented in IM tissues and could promote the expression of intestinal markers in gastric cells.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, miR-33a downregulates Snail and Slug levels, and inhibition of the Snail/Slug signaling pathway hinders migration and invasion of these cells (Fig. 2B) (42). Wu et al (43) have revealed that lncRNA CASC15 is a miRNA sponge in gastric cancer cells, as in hepatoma cells.…”
Section: Mir-33a and Its Role In Cancermentioning
confidence: 94%
“…Among them are miR-30a [70], miR-122 [95], miR-182 [115], and miR-203 [115] and miR-204 [116]. SLUG is targeted in in oral squamous cell carcinoma by miR-204 [116]; glioblastoma by miR-203 [117]; in lung cancer by miR-1 [118]; in breast cancer by miR-124 [119,120], miR-30a [70], miR-497 [121], miR-1271 [122], and miR-203 [123,124]; in gastric cancer by miR-33a [125]; in lung cancer by miR-218 [126]; in clear cell renal cell carcinoma by miR-1 [127]; in osteosarcoma by miR-124 [128]; and in gingival fibroblasts by miR-200b [129]. Similarly to SNAIL, miRNAs-SLUG action regulates EMT in cancer progression, as well as different processes, such as the modulation of cancer stem cells' activity.…”
Section: Regulation Of Slug Expression By Micrornasmentioning
confidence: 99%
“…Cancer/Cell Type References miR-1 lung cancer [118] miR-30a breast cancer [70] miR-33a gastric cancer [125] miR-124 breast cancer [119,120] osteosarcoma [128] glioma [130] miR-200b gingival fibroblasts [129] miR-203 glioblastoma [117] breast cancer [123,124] miR-204 oral squamous cell carcinoma [116] miR-218 lung cancer [126] miR-497 breast cancer [121] miR-630 dermal microvascular endothelial cells [131] miR-1271 breast cancer [122]…”
Section: Micrornamentioning
confidence: 99%